Subdural hematoma in glutaric aciduria type 1: high excreters are prone to incidental SDH despite newborn screening - Boy, Nikolas; Mohr, Alexander; Garbade, Sven; Freisinger, Peter; Heringer-Seifert, Jana; Seitz, Angelika; Kölker, Stefan; Harting, Inga (Journal of inherited metabolic disease, 2021)
Subdural hematoma (SDH) was initially reported in 20% to 30% of patients with glutaric aciduria type 1 (GA1). A recent retrospective study found SDH in 4% of patients, but not in patients identified by newborn screening (NBS). 168 MRIs of 69 patients with GA1 (age at MRI 9 days - 73.8 years, median 3.2 years) were systematically reviewed for presence of SDH, additional MR and clinical findings in order to investigate the frequency of SDH and potential risk factors. SDH was observed in eight high-excreting patients imaged between 5.8 and 24.4 months, namely space-occupying SDH in two patients after minor accidental trauma and SDH as an incidental finding in six patients without trauma. In patients without trauma imaged at 3 to 30 months (n = 36, 25 NBS, 27/9 high/low excreters), incidence of SDH was 16.7% (16% in NBS). SDH was more common after acute (33.3%) than insidious onset of dystonia (14.3%) or in asymptomatic patients (5.9%). It was only seen in patients with wide frontoparietal CSF spaces and frontotemporal hypoplasia. High excreters were over-represented among patients with SDH (6/27 vs 0/9 low excreters), acute onset (10/12), and wide frontoparietal CSF spaces (16/19). Incidental SDH occurs despite NBS and early treatment in approximately one in six patients with GA1 imaged during late infancy and early childhood. Greater risk of high excreters is morphologically associated with more frequent enlargement of external CSF spaces including frontotemporal hypoplasia, and may be furthered aggravated by more pronounced alterations of cerebral blood volume and venous pressure.